Komodifikasi Dai di Televisi: Kajian Ekonomi Politik Media - NURAENI, ASRI; MENTARI, RONA (Komunikator, 2013)
In every talent show on TV, labor commodification occurs not only on the creative team, but also on the contestants. Dai Muda Pilihan ANTV which was aired in 2011 was also full of commodification, particularly on the Dai (Islam preacher) as the contestants. In this study, the researcher wants to find out the processes and patterns of labor commodification, particularly the Dai in Dai Muda Pilihan ANTV. The method of the research is case study with in-depth interview, participant observation, and documentation as the data collection methods. The result shows that commodification in Dai Muda Pilihan ANTV occurred at pre-production, production, and postproduction. Therefore, the Dai who normatively have religious characters were encouraged to perform well and to entertain in accordance with the commercialization values of the television station which owned the program. Keywords: Dai Muda Pilihan ANTV, commodification, case study